2009
DOI: 10.1016/j.actamat.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of grain boundaries in creep strain accumulation

Abstract: To explain the seemingly complex results obtained when creep property measurements are described using power-law equations, it is commonly assumed that a transition from dislocation to diffusional creep processes occurs with decreasing applied stress. However, this assumption is negated by observations recorded for aluminium, copper and various particle-hardened alloys. Thus, all features of powerlaw behaviour for copper are predicted by new relationships based on normalization of the stress through the yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
3
23
0
1
Order By: Relevance
“…Therefore rather than seeking to identify 'steady-state' creep mechanisms, the focus of the Wilshire approach is directed at the deformation processes that define strain accumulation, and the damage mechanisms that accumulate and lead to eventual failure [9]. This allows a minimum creep rate to be defined as a decaying primary rate is offset by tertiary acceleration.…”
Section: An Alternative To Power-law Based Equationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore rather than seeking to identify 'steady-state' creep mechanisms, the focus of the Wilshire approach is directed at the deformation processes that define strain accumulation, and the damage mechanisms that accumulate and lead to eventual failure [9]. This allows a minimum creep rate to be defined as a decaying primary rate is offset by tertiary acceleration.…”
Section: An Alternative To Power-law Based Equationsmentioning
confidence: 99%
“…In an initial investigation of Al7010, Wilshire observed that power-law equations struggle to deal with precipitation strengthened materials [9] due to their inherit assumption of diffusional creep. As such a study was carried out on the nickel superalloy Waspaloy.…”
Section: Mechanisms Of Waspaloymentioning
confidence: 99%
See 3 more Smart Citations